MODEL BLENDED LEARNING BERBASIS WORDWALL MENINGKATKAN KEMAMPUAN LITERASI MATEMATIS DAN SELF-EFFICACY - Ramadhani Ramadhani; Suci Fitriani Nasution (Universitas Asahan, 2023)
The assessment that is currently being developed in the world of education is (KLM) or mathematical literacy ability and is measured from (SE) or self-efficacy of students. This study aims to determine whether students' abilities can increase with the model that has been implemented. The researcher used a quasi-experimental design with a